Landscape Assessment of Financial Flows: Lessons learned from pilot implementation - Louman, Bastian; Shames, S.; Pamerneckyte, G.; Owusu Ansah, M.; Koesoetjahjo, I. (2020)
Collaborative landscape initiatives demonstrate enormous potential to mobilize stakeholders across sectors, supporting them to work together on shared objectives. This meets a wide range of human needs, economic goals and ecosystem objectives. However, implementing these partnerships is challenging. Perspectives, values and ways of working differ greatly among partners; in many cases there is a legacy of misunderstanding and distrust. Strategies and tools are needed to overcome the resulting tendency for stalemate and conflict.